(untitled) (Research, Society and Development, 2021)
Objective: To describe the epidemiological profile, the spatial distribution of leprosy cases and the service quality of a Family Health Strategy (FHS) located in Belém, Pará state, from 2008 to 2015. Methodology: Cross-sectional quantitative study, based on Information System and Notifiable Diseases files. The studied population consisted of leprosy cases resident in Belém, notified by an FHS. Through the Kernel method, the thematic map with the density of cases was created. The data were presented in the form of tables and graphs in Microsoft Office Excel 2013 and thematic maps in the software Qgis, 2017. Results: Of the 14 cases in the period, the highest occurrence of the disease was in the male gender (71.43%), brown skin color (42.86%), with low education (57.14%) and with a predominance of the age group of 20 to 39 years (43%). The first and last years of the study showed the lowest rate of detection of the disease (0.4 / 1,000 inhab.), While in 2013 and 2014 the most expressive value of the series was recorded (1.6 / 1,000 inhab.). The Kernel method showed different densities of interest on the surface of the area assigned to the ESF, with care for cases that resided outside it (42.86%). Conclusion: The persistence of the endemic disease and the high proportionality of attendance to leprosy cases outside the area assigned to the FHS demonstrate the importance of this service and allow the directing of planning to the population at greatest risk of illness.